SIMULATION OF WORKING MODES OF THE ELECTRICAL DRIVEOF A LIFTING CRANE WINCHES IN MATLAB - BABIY, Sergiy; MOSHNORIZ, Mykola; PROCENKO, Dmytro; PAYANOK, Oleksandr; ZHUKOV, Oleksiy (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Among the most common mechanisms in the industry are lifting machines of various types and designs. They are widely used in construction and assembly, repair, warehouse and other works related to lifting and moving large and heavy loads. The main and most energy-intensive mechanism of lifting machines is the lifting winch. The electric drive of the lifting winch must meet the increased operational requirements and ensure the performance of the given speed diagram, the necessary dynamics of work and high reliability in the operating modes. The energy indicators of the electric drive of the lifting winch mainly determine the energy indicators of the machine as a whole, therefore, due attention should be paid to the issue of designing the electric drives of the lifting winches. It is worth noting that the kinematic connections of the lifting winch are not absolutely rigid, which determines the occurrence of oscillations in the system as a result of dynamic forces. It is the presence in the electromechanical system of the lifting winch of elements with high inertia that causes the appearance of elastic oscillations during any transient process in this system. The presence of elastic oscillations in the mechanical system of the electric drive distorts the speed graphs of the system and leads to force pulsations. Elastic oscillatory processes in mechanisms lead to unpredictable behavior of the system and can cause emergency situations. Thus, taking into account the elastic properties of the mechanical system during its design will improve the efficiency and reliability of its operation. The results of the research carried out in the work contain the analysis of static loads of lifting winches of lifting and transport mechanisms and a generalized mathematical model of the crane lifting winch. On the basis of the proposed mathematical model, a structural diagram of a lifting winch was developed and implemented as a computer model in the form of a Matlab Smulink PPP library block. The mathematical and computer models presented in the work allow obtaining correct results in the entire range of loads, taking into account the change in the efficiency of the mechanical transmission when the loads and the direction of transportation change, and also take into account the influence of the elastic connection between the drive motor and the actuator. The use of the proposed models will significantly simplify the process of designing the power electric drive of lifting winches of cranes.
Keywords: lifting winch; mathematical model; static moment; electric drive